PERANCANGAN SISTEM MONITORING PADA ALAT PENGATUR SUHU DAN KELEMBABAN KANDANG PUYUH BERBASIS INTERNET OF THINGS (IOT) (Studi Kasus : Peternakan Bang Ade) - Dicki Fernando Aurellianto; Munawaroh (CV. Multi Kreasi Media, 2023)
The temperature and humidity control system is very helpful for breeders to maintain the temperature of the quail cage to remain stable in order to achieve success for breeders. Apart from that, the system can help both in terms of time efficiency and human labor because the system works automatically. The microcontroller will give instructions to turn off or turn on the humidity sensor where the sensor will read the room temperature of the quail cage then instruct Arduino to turn on the switch and turn on the light/fan which will automatically in the livestock cages that experience increased air humidity. The proposed method for developing a temperature and humidity monitoring system is the observation method. Data collection is carried out directly on the object of the problem in the ade maulana quail farm. The author made direct observations when the farm manager carried out mointoring on quails. Automatic control design and temperature monitoring of quail cages by utilizing Internet Of Things (IoT) technology using the Blynk application integrated with the NodeMCU ESP8266 module equipped with a DHT11 temperature sensor which functions as a temperature detector in the cage. In addition, this tool is equipped with a 16x2 LDC to display the results of temperature detection, as well as a relay that functions to control the fan and turn on the light bulb in the cage.